Labor Limites. Riconoscere, vivere e riprogettare i limiti - Bin, Sara (Tratti geografici. Materiali di ricerca e risorse educative, 2016)
This edited volume contains some reflections on the concept of limit, emerged from the third National Workshop of Padua (May 2014) promoted by the Italian Association of Geography Teachers. The goal is to create a dialogue between authors of different scientific fields around one of the most relevant and critical topics today.